Immunization of cattle against tick, Boophilus microplus - GHOSH, S; KHAN, M H (The Indian Journal of Animal Sciences, 2013)
Two antigens, viz. tick extract supernatant antigen (TESA) and larval antigen (LA), were prepared from 109 each of partially fed adults and unfed larvae of Boophilus microplus. Calves in 2 batches of 6 and 8 were immunized with 53 and 45 mg of protein in 3 divided doses. With enzyme linked immuilosorbent assay (ELISA), a significant antibody (P